Clinicopathological characteristics, evolution, and treatment outcomes of hormone receptor-negative/HER2-low metastatic breast cancer: a pooled analysis of individual patient data from three prospective clinical trials - Hu, Shihui; Zhao, Yannan; Xie, Yizhao; You, Shuhui; Hu, Xichun; Zhang, Jian; Wang, Leiping; Cao, Jun; Gong, Chengcheng; Wang, Biyun (Frontiers in Endocrinology, 2024)
Objective: With the approval of trastuzumab deruxtecan for the treatment of unresectable/metastatic HER2-low breast cancer, human epidermal growth factor receptor 2 (HER2)-low has emerged as a clinically actionable biomarker. There is an urgent need for a deeper understanding of HER2-low patients. Therefore, this study was conducted to explore the clinicopathological characteristics, the evolution of HER2low status, and its impact on the prognosis of hormone receptor (HoR)-negative/ HER2low metastatic breast cancer (MBC) patients.Methods: This pooled analysis included 350 metastatic triple-negative breast cancer (mTNBC) patients who received first-line platinum-based chemotherapy at Fudan University Shanghai Cancer Center from November 2007 to July 2022. Patients were categorized into HER2-0 and HER2-low groups based on their HER2 status. Baseline clinicopathological characteristics, evolution of HER2 status between primary and metastatic lesions, and treatment efficacy were compared between the two groups.Results: Among the 350 mTNBC patients, 34.9% (122/350) were HER2-low and 65.1% (228/350) were HER2-0. Significant differences were observed between HER2-low and HER2-0 patients in terms of age and menopausal status. HER2-low patients were older (54 vs. 49 years, p=0.002) and had a lower proportion of premenopausal patients (32.8% vs. 52.6%, p<0.001) compared to HER2-0 patients. No significant differences were observed in progression-free survival (PFS) and overall survival (OS) between HER2-low and HER2-0 patients receiving first-line platinum-based chemotherapy